Comprehensive management of children and adolescents with type 1 diabetes mellitus through personalized physical exercise and education using an mHealth system: The Diactive-1 study protocol - Hormazábal-Aguayo, Ignacio; Muñoz-Pardeza, Jacinto; López-Gil, José Francisco; Huerta-Uribe, Nidia; Chueca-Guindulain, María J.; Berrade-Zubiri, Sara; Burillo Sánchez, Elisabet; Izquierdo, Mikel; Ezzatvar, Yasmin; García-Hermoso, Antonio (Frontiers in Endocrinology, 2024)
The use of new technologies presents an opportunity to promote physical activity, especially among young people with type 1 diabetes (T1DM), who tend to be less active compared to their healthy counterparts. The aim of this study is to investigate the impact of a personalized resistance exercise program, facilitated by the Diactive-1 App, on insulin requirements and treatment adherence among children and adolescents diagnosed with T1DM.A minimum of 52 children and adolescents aged 8-18 years, who were diagnosed with T1DM at least 6 months ago, will be randomly assigned to either a group engaging in an individualized resistance exercise program at least 3 times per week over a 24-week period or a waiting-list control group. The primary outcome will be the daily insulin dose requirement. The secondary outcomes will include glycemic control, cardiometabolic profile, body composition, vascular function, physical fitness, 24-hour movement behaviors, diet, and psychological parameters. The usability of the app will also be assessed.Ethical approval to conduct this study has been granted by the University Hospital of Navarra Research Board (PI_2020/140). Parents or legal guardians of minors participating in the study will provide written consent, while children and adolescents will sign an assent form to indicate their voluntary agreement. The trial's main findings will be shared through conference presentations, peer-reviewed publications, and communication directly with participating families. This study aims to offer valuable insights into the holistic management of children and adolescents with T1DM by utilizing personalized exercise interventions through an mHealth system.